Increasing the grind size for effective liberation and flotation of a porphyry copper ore by microwave treatment - Batchelor, A.R.; Jones, D.A.; Plint, S.; Kingman, S.W. (Elsevier, 2016)
In this paper, mineralogy, grain size, dissemination, textural consistency and mineral associations were determined for a commercially exploited porphyry copper ore using a Mineral Liberation Analyser (MLA). The ore was subjected to high power density microwave treatments in a single mode cavity at 15 kW and approximately 2 kW h/t. The untreated and microwave-treated samples were subsequently milled to two grind sizes near the nominal plant grind size and a size-by-liberation analysis performed. The analysis revealed that equivalent liberation could be obtained at a grind size approximately 50–60 μm coarser than the nominal plant grind due to the microwave treatment. Flotation testing indicated that an increase in copper recovery of approximately 1% could be achieved, or that a grind size increase of approximately 30 μm may potentially yield equivalent copper recovery due to the microwave-enhanced liberation observed. However, statistical analyses demonstrated that it is difficult to attain confidence in recovery increases of approximately 1% even when conducting batch flotation tests in triplicate. The ore under investigation had previously been shown to produce only modest average reductions in strength (∼8%) under similar microwave treatment conditions due to a prevalence of many unfavourable textures. However, the preferential association of copper minerals with a hard matrix mineral (quartz) and a hard microwave-absorbent mineral (pyrite) resulted in a significant change in liberation behaviour.